PENGARUH TRAINING, MOTIVASI DAN BEBAN KERJA TERHADAP PENINGKATAN PRODUKTIVITAS KERJA PEGAWAI DI LINGKUNGAN AIRNAV INDONESIA CABANG MEDAN - Cahya Leswaeny; Albenny Hevi Damanik; Erwin Parlindungan Nasution; Julia Inda Sari; Jumasri . (Universitas Islam Islam Sumatera Utara, 2020)
This research is based on the importance of the role of air transportation in supporting national development, therefore efforts are needed in realizing and improving aviation safety which is a service product, especially at Medan's Kualanamu airport. This study uses independent variables, namely: Training (X1), motivation (X2), workload (X3), and increased productivity of Airnav Indonesia employees in Medan branch as the dependent variable. Collecting research data using a questionnaire method distributed to 72 employees who work as Air Traffic Controllers who are Airnav Indonesia employees who are tasked with providing direct flight traffic services to provide air traffic guidance services, especially for aircraft flight traffic, such as aircraft. flying, helicopters and more. The results of the analysis and the t test show that the variable training has no significant impact on productivity. Meanwhile, motivation and workload have a significant positive effect on employee productivity in the Medan branch of the Airnav Indonesia work environment. In testing the hypothesis based on the F test or Anova test, it is known that the value of Fcount (35,508) Ftable (2.74) with a significance level of 0,000 0.05, so that H0 is rejected and H1 is accepted. This means that training, work motivation, and workload simultaneously have a positive and significant effect on the work productivity of Air Traffic Control (ATC) employees in Airnav Indonesia Medan Branch. The result of the coefficient of determination (R2) is 0.595. meaning that 59.5% of the dependent variable (work productivity) is influenced or explained by the independent variables, namely training, motivation and workload. The remaining 40.5% (100% - 59.5%) is influenced or explained by other variables outside the variables not used in this study.